Biology of Crocidura sibirica Dukelsky, 1930 in the southern West Siberia - Luchnikova, Ekaterina M.; Ilyashenko, Vadim B.; Kovalevskiy, Alexander V.; Zubko, Kirill S.; Vdovina, Evgeniya D.; Teplova, Natalya S. (Altai State University, 2023)
Our paper reflects the data of a comprehensive study of the main biological characteristics of the Siberian shrew Crocidura sibirica Dukelsky, 1930. 921 specimens were examined for the period 1978–2020. It has been found that the Siberian shrew is attracted to habitats that have been significantly disturbed by human activity (logging sites, hayfields, reclaimed coal dumps, burned areas), but avoids completely degraded areas and urban ecosystems. It reaches its maximum abundance in the low-mountain belt of the Kuznetsk Alatau in hay meadows. The population of the Siberian shrew is subject to cyclic fluctuations with a frequency of 3–4 years. Seasonal activity peaks in mid-August and September, with breeding in the second half of summer and early fall. Among the one-year-old animals, the predominance of males is observed. The diurnal activity of the Siberian shrew is polyphasic, mainly nocturnal. Peaks of highest activity were observed at 23–24 hours and 6–9 hours. In terms of running speed, digging ability, and swimming ability, the Siberian shrew is significantly inferior to its trophic competitors, the other shrews. In interspecific encounters, neutral, friendly interactions predominate; aggression is ritualized. In intraspecific encounters with large shrews, the Siberian shrew will occupy a shelter and attempt to drive an opponent from it. The food spectrum is based on the imaginal and larval stages of insects, arachnids, and centipedes. Among insects, ground beetle larvae, Brachycera, and Hymenoptera are the most preferred foods. The identified food spectrum corresponds to the biotopic distribution of invertebrates, indicating the absence of food selectivity. The trophic spectrum of the C. sibirica overlaps significantly with that of sympatric species of other shrews. Given the significant overlap of the spatial ecological niche, it can be assumed that the Siberian shrew avoids competitive interactions for food resources due to the mismatch of the peak of seasonal activity. Under the influence of competitive ...